Reclassification of type 2 diabetes to type 1 diabetes in Asturias (Spain) between 2011 and 2020 - Raúl Rodríguez Escobedo; Carmen Lambert; Paula Morales Sánchez; Elías Delgado Álvarez; Edelmiro Menéndez Torre (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Differentiating between type 1 diabetes (T1D) and type 2 diabetes (T2D) can be difficult in adults. The aim of this study was to determine the frequency of diagnostic reclassification from T2D to T1D, the characteristics of the patients and the impact on the management of the disease. Methods Observational and descriptive study including patients diagnosed with T1D in Asturias (Spain) between 2011 and 2020 who had been considered as T2D for at least 12 months. Results A total of 205 patients were included, representing 45.3% of those diagnosed with T1D over 30 years of age. Median time of evolution as T2D was 7,8 years. The age was 59.1 ± 12.9 years. BMI was > 25 kg/m2 in 46.8% of patients. HbA1c was 9.1 ± 2.1%, 77 ± 22 mmol/mol, and 56.5% were using insulin. Pancreatic antibodies were present in 95.5%, the most frequent being GAD, 82.6%. At 6 months, basal insulin use increased from 46.9 to 86.3%, and HbA1c decreased, 9.2 ± 2.0%vs7.7 ± 1.2%, 77 ± 22vs60 ± 13 mmol/mol; p < 0.0001. Conclusions Diagnosis as T2D in patients with T1D in adults is common. Age, BMI, insulin use and other clinical features are not definitely discriminatory. GAD is the antibody of choice in case of diagnostic suspect. Reclassification has important implications for metabolic control.